Making the case for resistance training in improving vascular function and skeletal muscle capillarization - McIntosh, Mason C.; Anglin, Derick A.; Robinson, Austin T.; Beck, Darren T.; Roberts, Michael D. (Frontiers in Physiology, 2024)
Through decades of empirical data, it has become evident that resistance training (RT) can improve strength/power and skeletal muscle hypertrophy. Yet, until recently, vascular outcomes have historically been underemphasized in RT studies, which is underscored by several exerciserelated reviews supporting the benefits of endurance training on vascular measures. Several lines of evidence suggest large artery diameter and blood flow velocity increase after a single bout of resistance exercise, and these events are mediated by vasoactive substances released from endothelial cells and myofibers (e.g., nitric oxide). Weeks to months of RT can also improve basal limb blood flow and arterial diameter while lowering blood pressure. Although several older investigations suggested RT reduces skeletal muscle capillary density, this is likely due to most of these studies being cross-sectional in nature. Critically, newer evidence from longitudinal studies contradicts these findings, and a growing body of mechanistic rodent and human data suggest skeletal muscle capillarity is related to mechanical overload-induced skeletal muscle hypertrophy. In this review, we will discuss methods used by our laboratories and others to assess large artery size/function and skeletal muscle capillary characteristics. Next, we will discuss data by our groups and others examining large artery and capillary responses to a single bout of resistance exercise and chronic RT paradigms. Finally, we will discuss RT-induced mechanisms associated with acute and chronic vascular outcomes.